2011
DOI: 10.1088/1748-6041/6/1/015010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the tissue reaction to a new bilayered collagen matrix in vivo and its translation to the clinic

Abstract: This study evaluates a new collagen matrix that is designed with a bilayered structure in order to promote guided tissue regeneration and integration within the host tissue. This material induced a mild tissue reaction when assessed in a murine model and was well integrated within the host tissue, persisting in the implantation bed throughout the in vivo study. A more porous layer was rapidly infiltrated by host mesenchymal cells, while a layer designed to be a barrier allowed cell attachment and host tissue i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
180
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(197 citation statements)
references
References 26 publications
11
180
1
5
Order By: Relevance
“…Previous histological studies from our laboratory suggested that PA gels can remain in recipient tissues for up to a month (39,40). Here, to track and quantify the biomimetic scaffold's degradation in vivo over time, we made use of scaffolds containing the Gd(III) label (36) (Fig.…”
Section: Development Of An Injection Apparatus To Form Aligned Biomimmentioning
confidence: 99%
“…Previous histological studies from our laboratory suggested that PA gels can remain in recipient tissues for up to a month (39,40). Here, to track and quantify the biomimetic scaffold's degradation in vivo over time, we made use of scaffolds containing the Gd(III) label (36) (Fig.…”
Section: Development Of An Injection Apparatus To Form Aligned Biomimmentioning
confidence: 99%
“…Mucograft ® is a resorbing porcine matrix composed of type I and type III collagen, which is used for soft tissue augmentation in both guided tissue and bone regeneration procedures. It is composed by a porcine collagen bilayer structure (4,5). The compact layer, which consists of compact collagen fibers with occlusive cellular properties, allows tissue adherence as a prerequisite for favorable wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…This layer not only protects against bacterial infiltration during open healing conditions, it also contains adequate elastic properties to accommodate suturing. The second layer consists of a thick, porous, spongy collagen structure, which is placed next to the host tissues to facilitate organization of the blood clot and promote neoangiogenesis and tissue integration (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The material persisted in the tissue throughout the study. At the same research, results demonstrate great potential to reverse tissue recession and promote more healthy gingival tissue [15]. Collagen matrix can enhance oral soft tissue healing compared with spontaneous healing during the first week, based on clinical observations that the two distinct structures paved the way to improve the healing by an early stabilization of the coagulum (matrix function) [16].…”
Section: Discussionmentioning
confidence: 98%